2010
DOI: 10.3109/10715761003692511
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of metallothionein on oxidative stress-induced DNA damage

Abstract: Metallothioneins (MTs) are a family of low molecular weight proteins with a high cysteine and metal ion content. They are found in most cells and tissues and can be induced by a number of substances, including various forms of oxidative stress. MTs play a central role in essential trace element homeostasis and in metal detoxification. Because of their peculiar structure, characterized by a large content of thiol groups, MTs also act as a potent antioxidant by protecting against various injuries resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 56 publications
3
69
0
1
Order By: Relevance
“…Using mZDF rats, angiotensinogen was recently shown to be induced in mesangial cells via ROS/ ERK/JNK pathways (Ohashi et al 2010), and similar mechanisms might be operating in the liver. MT1 is a potent cellular antioxidant that plays important roles in essential trace element homeostasis, metal detoxification and in the protection against various injuries resulting from ROS (Chiaverini & De Ley 2010), including the development of diabetes and its complications (Ohly et al 2000, Cai 2004, Song et al 2005, Ayaz et al 2006, Tang et al 2010. It has also been shown that levels of MT1 are increased in the livers of diabetic rats (Cai et al 2002), which is in agreement with the results obtained in this study.…”
Section: Resultssupporting
confidence: 82%
“…Using mZDF rats, angiotensinogen was recently shown to be induced in mesangial cells via ROS/ ERK/JNK pathways (Ohashi et al 2010), and similar mechanisms might be operating in the liver. MT1 is a potent cellular antioxidant that plays important roles in essential trace element homeostasis, metal detoxification and in the protection against various injuries resulting from ROS (Chiaverini & De Ley 2010), including the development of diabetes and its complications (Ohly et al 2000, Cai 2004, Song et al 2005, Ayaz et al 2006, Tang et al 2010. It has also been shown that levels of MT1 are increased in the livers of diabetic rats (Cai et al 2002), which is in agreement with the results obtained in this study.…”
Section: Resultssupporting
confidence: 82%
“…MTs are a class of low-abundance cytoplasmic SH-rich proteins binding a variety of metals, iron included, 30 whose upregulation is highly protective against a number of harmful conditions, in particular those in which oxidative stress is involved. 29,[53][54][55][56][57] These proteins are often overexpressed in various cancers, making them more resistant to irradiation and drugs that induce oxidative stress. 58 In the present work, MT1A and MT2A were found poorly expressed in HTC cells under basal conditions, but were easily upregulated by ZnCl 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the average person's intake of cadmium is only ϳ1 to 30 g/person/ day via food and water, with an additional 2 to 30 g of cadmium per person per day among cigarette smokers (a single cigarette carries ϳ1-2 g of cadmium) (Andersson et al, 1986; Agency for Toxic Substances and Disease Registry, 2008;Pan et al, 2010), it has an exceedingly long half-life, approximately 20 to 40 years in humans (Kjellström and Nordberg, 1978;World Health Organization, 2000;Wong et al, 2010b) and Ͼ200 days in rodents (Webb, 1975). Cadmium accumulates mostly in the liver and kidney but also in the testes (Waalkes et al, 1992;Jä rup and Akesson, 2009), largely because of high concentrations of metallothioneins [cysteine-rich low molecular mass metal-binding proteins localized to the membrane of the Golgi apparatus that protect cells from cytotoxicity of heavy metals (such as copper, selenium, and zinc) and xenobiotics (such as cadmium, mercury, silver, and arsenic) by binding to these metals through the thiol group of its cysteine residues] in these organs (Dalton et al, 1996;Siu et al, 2009a;Chiaverini and De Ley, 2010;Vesey, 2010;Wong et al, 2010b). As such, significant and harmful amounts of cadmium can indeed build up in a person over a period of time, overwhelming the capacity of metallothioneins.…”
Section: B the Cadmium Modelmentioning
confidence: 99%